Differentiation between Call Fleming syndrome and nervous system vasculitis - Ribeiro, Fernanda Cristina Poscai; Rodrigues, Everton Lopes (Headache Medicine, 2022)
Introduction Call Fleming syndrome is a reversible cerebral vasoconstriction syndrome of idiopathic etiology that causes thunderclap headache. It is a condition with a good prognosis, but clinically and radiologically similar to other diseases, such as nervous system vasculitis. Objectives To bring clinical, radiological and laboratorial aspects of Call Fleming Syndrome and nervous system vasculitis and provide the differentiation of both. Methodology The research is an integrative review, carried out in June 2022, using the SciElo and Pubmed databases. From the keywords: Call-Fleming syndrome) AND (Diagnosis), (Case report), (Radiology), the clinical, laboratorial and radiological profile of the Call-Fleming Syndrome was traced while the keywords (Nervous System) AND (Vasculitis) AND (Diagnosis), (Case report), (Radiology) were used to CNS vasculitis. Then, from case reports, radiology articles and laboratory analyses, the diseases in question were compared in terms of similarities and differences. Results Both pathologies are similar from a clinical point of view: they are frequent causes of thunderclap headache, a sudden and severe headache that reaches its maximum intensity within 1 minute. Some patients with Call-Fleming Syndrome may present several neurological deficits, the more frequents in case reports are hemiparesis, hemianopia, and loss of balance. The disease has a limited course that lasts from 1 to 3 months, however, its main complications are hemorrhages and cerebral infarction. The age group affected in the reported cases ranges from 10 to 76 years and there is a slight predominance of cases in women. (To see the complete abstract, please, check out the pdf).